The Association Between Polymorphisms in Cell-Cycle Genes and Mitochondrial DNA Copy Number in Coke Oven Workers - Wang, Yuping; Tan, Jiebing; Wang, Wei; Duan, Xiaoran; Lappe, Brooke; Shi, Liuhua; Yang, Yongli; Shi, Xuezhong (Frontiers in Public Health, 2022)
The mitochondrial DNA (mtDNA) copy number is a vital component in maintaining normal mitochondrial function. It is affected by environmental and occupational exposures, as well as polymorphisms in nuclear genes. Nonetheless, the specific roles of polymorphisms in cell-cycle genes and mtDNA copy number are still unknown. This study enrolled a sample of 544 coke oven workers and 238 non-exposed controls so as to assess the effect of exposure of coke oven emissions (COEs) and polymorphisms in cell-cycle genes on the mtDNA copy number. We found that the mtDNA copy number in the exposed group (0.60 ± 0.29) was significantly lower than that in the control group (1.03 ± 0.31) (t =18.931, P < 0.001). The analysis of covariance showed that both the rs1801270 (CA+CC) and the rs1059234 (CT+CC) in p21 gene were associated with lower mtDNA copy number in the exposed group (P = 0.001). Generalized linear models indicated COEs-exposure (β = −0.432, P < 0.001) and rs1059234 (CT+CC) in p21 gene (β = −0.060, P = 0.024) were the factors in mtDNA copy number reduction. In conclusion, this study suggests that the decrease of the mtDNA copy number is associated with COEs-exposure and the rs1059234 (CT+CC) in the p21 gene.